Early‐onset familial hypercholesterolemia: A case of extensive xanthomas and premature coronary artery disease - Harsimran Kalsi; Ankur Singla; Sukhjot Kaur; Amogh Verma; Nathnael Abera Woldehana; Sarvesh Rustagi; Mahendra Pratap Singh (Clinical Case Reports, 2024)
Key Clinical Message Early recognition and management of familial hypercholesterolemia (FH) are crucial, especially in patients with extensive xanthomas and premature coronary artery disease. Prompt diagnosis and aggressive lipid‐lowering therapy can significantly reduce morbidity and mortality rates. Careful clinical assessment in resource‐limited settings is essential for optimal outcomes. Abstract Familial hypercholesterolemia (FH) is an autosomal dominant inherited disorder that causes chronically elevated levels of low‐density lipoprotein (LDL) cholesterol. Based on LDL levels, FH can be heterozygous or homozygous, further established through clinical features, laboratory findings, and genetic analysis. Elevated cholesterol levels cause atherosclerosis, coronary artery disease, myocardial infarction, and sudden death. Xanthomas are a clinical manifestation of FH that reveal the underlying systemic genetic disease. We present the case of a 47‐year‐old male with triple vessel coronary artery disease and widespread xanthomas, diagnosed with homozygous FH based on “The Dutch Lipid Clinic Network Diagnostic Criteria for Familial Hypercholesterolemia.” Lifelong therapy with lipid‐lowering medications and lifestyle changes is necessary in such cases.